The role of patients and carers in diffusing a health‐care innovation: A case study of "My Medication Passport" - Susan Barber; Catherine French; Rachel Matthews; Derryn Lovett; Tom Rollinson; Fran Husson; Margaret Turley; Julie Reed (Wiley, 2019)
Abstract Background Patients are increasingly recognized as playing important roles in improving health services. Little is known about the mechanisms by which patients develop and diffuse local innovations in a complex health‐care system. Objective To ascertain how diffusion of an innovation, My Medication Passport, occurred and roles played by patients in it. Design Case study: quantitative mapping of innovation's diffusion and analysis of the routes and occupations of those through whom the innovation spread; documentary analysis; reflective assessment of patient's roles. Setting and participants NHS Trusts, third sector organizations, patients and health‐care professionals. Interventions studied Co‐produced action to raise awareness and influence use of the innovation; order database which enabled ease of access to the innovation. Main outcome measures Geographical spread of innovation; occupations of individuals; types of organizations using the innovation. Results The innovation spread from initial development and use in Northwest London across the UK and beyond. Key roles played by patients were as follows: co‐producer; advocate; relationship builder; relationship broker; planner; presenter; awareness raiser; trainer; networker. Patients identified and introduced potential audiences and users to MMP, using social, organizational, sectoral, lay and professional networks to do so. They organized a range of awareness‐raising and communication activities, monitored feedback, evaluated the impact and responded to new interest. Discussion and conclusions The roles of patients in diffusing innovations are under‐recognized. Collaborative working between patients, carers and health‐care professionals in planning and progressing the use and supporting diffusion of the innovation was important. Principles described in this study are relevant to progressing other patient‐led ideas for innovative changes relating to health service development.